XML hacks - Fitzgerald, Michael, 1957- (O'Reilly, 2004)
This is a practical guide that distills years of ingenious XML hacking into a complete set of tips, tricks and tools for those who want to leverage the untapped power of XML. It includes many real-world projects that illustrate how to define, create, read and manipulate XML documents.